2016
DOI: 10.1515/agri-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Antioxidant Content of Broccoli Sprouts Using Essential Oils During Cold Storage

Abstract: Broccoli sprouts are natural functional foods for cancer prevention because of their high content of glucosinolate and antioxidant. Sprouts and mature broccoli are of potential importance in devising chemoprotective strategies in humans.The aim of the investigation was to study the effect of essential oils on broccoli seed germination, increase their antioxidant content and determine the glucosinolate concentration and other phytochemical parameters in 3-day -old sprouts during cold storage at 4°C and 95% RH f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Their phenolic profile composed mostly of sinapic acid, gallic acid, flavonoids (quercetin and kaempferol), and other hydroxycinnamic acids (chlorogenic, caffeic acid, and ferulic acids) ( Table 3). In general, total phenolic and flavonoid contents were determined to be in the ranges of 74-453 mg per 100 g of FW and 95-105 mg per 100 g of FW, respectively [43,65,77].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Their phenolic profile composed mostly of sinapic acid, gallic acid, flavonoids (quercetin and kaempferol), and other hydroxycinnamic acids (chlorogenic, caffeic acid, and ferulic acids) ( Table 3). In general, total phenolic and flavonoid contents were determined to be in the ranges of 74-453 mg per 100 g of FW and 95-105 mg per 100 g of FW, respectively [43,65,77].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The anti-oxidant role of broccoli has been identified in the human colon fiber exposed to oxidative stress [70] . Broccoli demonstrated potential anti-tumor activity [71] due to its high glucosinolate content. The sulforaphane consumption of broccoli is also considered to shield DNA from extremely reactive electrophilic degradation through enhanced anti-oxidant activity and inflammation [72] .…”
Section: Anti-hepatocellular Carcinoma Effects Of Traditional Chinesementioning
confidence: 99%
“…All of these have previously been reported to contain high glucosinolate levels [ 35 ]. In addition, previous studies reported that glucosinolate production varies between cultivars [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%